Analysis Of Knowledge Sharing And Absoprtive Capacity Models On Business Performance In Msmes Engaged In Fried Foods In Bekasi City - Syahyono, Syahyono; Purwitasari, Diah Ayu; Rahmawati, Inestia; Wati, Az Zahra Putri Setyo; Atika, Putri Amelia (Jurnal Ilmiah Wahana Pendidikan, 2025)
The food industry, especially fried foods, plays an important role in Bekasi's economy, which is known as the centre of culinary production. Companies face increasingly complex challenges as the industry grows rapidly, such as changing consumer preferences, fierce competition, and rapid market dynamics. With the increasing complexity of competition in many industries, including the food industry, businesses must constantly look for methods to strengthen their capacity to adapt to innovations and changes in the market. Knowledge Sharing and Absorption Capacity support each other in improving the company's innovation and operational efficiency, which directly impacts business performance. Innovation and operational efficiency were significantly influenced by absorption capacity, i.e. the ability to receive, evaluate, and use external information. This study shows that the absorption capacity is strong and bagged.